Redescription of Sphenanthias whiteheadi Talwar (Perciformes: Cepolidae) with DNA barcodes from the southern coasts of India - Bineesh, K. K.; Sajeela, K. A.; Akhilesh, K. V.; Pillai, N. G. K.; Abdussamad, E. M. (Zootaxa, 2011)
A very rare bandfish, Sphenanthias whiteheadi Talwar 1973, is re-discovered and described from the southwest and southeast coasts of India for the first time after its original description and the rarity of the fish is challenged. A mitochondrial COI barcode sequence was generated for the specimen.